The effect of within-firm vertical pay disparity in occupational safety. (January 2022) - Ramírez, Cristian; Tarziján, Jorge; Singer, Marcos
Highlights: The compensation structure of firms is related to workplace injuries and days lost. Increasing within-firm pay disparity leads to more injuries and days lost. The relationship between pay disparity and injuries is weaker in state-owned firms. Gender matters for the analysis of compensation structure and workplace injuries. The effect of pay disparity on injuries is different at different salary levels. Abstract: Greater vertical pay disparity is associated with compensation schemes that reward relative performance. Considering tournament theory as a leading framework for those schemes, along with boosting productivity, they are likely to increase workers' willingness to exert effort at the risk of injuries or occupational sickness. We find evidence of such pervasive effect on a novel database that includes more than 110, 000 Chileans firms. For workers in the bottom half of the wage distribution, an increment of one standard deviation in within-firm vertical pay disparity is associated with an increase of around 10% in the number of injuries and almost 19% in the number of days lost. These results are negatively moderated by the proportion of female employees and state ownership.